Productive And Reproductive Performances Of Indigenous And Broiler Parent Line Crossed With Indigenous Chickens - Pathak, S. S.; Kalita, N.; Barua , N. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was conducted to compare the productive and reproductive performances of indigenous chicken and a flock of broiler parent line X indigenous chicken in deep litter system of rearing. The body weights (g) at different ages were significantly (P < 0.05) higher in group V than indigenous groups, but among indigenous groups no significant difference was observed. The birds of group V matured earlier than that of indigenous groups. Among indigenous groups, group III showed the earliest age at sexual maturity followed by group I, group IV and group II . The egg production was significantly higher in group V than indigenous groups. Among indigenous groups, group III showed higher egg production followed by group I, group IV and group II . From this study it can be concluded that the productive and reproductive performances in terms of body weight, age at sexual maturity and egg production were found to be far better in crossed (broiler parent line X indigenous chicken) than indigenous groups. Among indigenous chicken groups, group II (black with brown hackle), crossed chickens (broiler parent line X indigenous) was found to be higher in growth performances, earlier age at sexual maturity and higher egg production respectively.
Keywords: Indigenous chicken; Broiler parent line; Plumage colour pattern; Body weight; Age at sexual maturity; Egg production